The Effect of Self-Regulated Learning on Academic Procrastination in Mathematics of Public Junior High School Students in Pekanbaru City - Tengku, Tengku Abdani Murazanty; Amelia, Sindi (Edupedia Publisher, 2025)
This study aims to determine the effect of self-regulated learning on academic procrastination in mathematics of public junior high school students in Pekanbaru City. This study is a quantitative study with a causal associative research type. The population in this study were all public junior high school students in Pekanbaru City, while the sample in this study amounted to 329 students consisting of 3 public junior high schools in Pekanbaru City, namely Junior High School 10 Pekanbaru, Junior High School 18 Pekanbaru, and Junior High School 33 Pekanbaru with a sampling technique of proportionate stratified random sampling. Data were collected using a questionnaire and analyzed using a simple linear regression analysis technique with the help of the IBM SPSS Statistics 26 program. The results showed a Sig. value of 0,000 (0,000 < 0,05) and tcount > ttable (–) (24,272 > 1,967) with a negative influence direction which means that the higher the self-regulated learning, the lower the academic procrastination and vice versa. Self-regulated learning has an R Square value of 0,643 which means that the contribution of self-regulated learning to academic procrastination is 64,3% and the remaining 35,7% is influenced by other factors. Thus it can be concluded that the effect of self-regulated learning on academic procrastination in mathematics of public junior high school students in Pekanbaru City.